THE GROWTH OF NUCLEATION LAYERS FOR HIGH-QUALITY DIAMOND CVD FROM AN RF PLASMA - Jackman, R; Beckman, J; Foord, J (1995)
Capacitively coupled radio frequency (cc-RF) plasmas offer significant advantages over microwave-induced plasmas for the growth of large-area homogeneous thin films. However, conventionally designed cc-RF sources lead, at best, to extremely poor-quality material when diamond growth is attempted. The first complete diamond overlayer to be grown with cc-RF is reported here, where a novel magnetically enhanced source with ring electrodes has been used. In addition, nanocrystalline diamond can be grown whose Raman spectra closely resemble that of a nucleation layer grown by bias-enhanced nucleation methods during MW PECVD. The potential of this technique for the growth of nucleation layers and high-quality diamond films is discussed. © 1995.